First Principles Calculation of epsilon-Phase of Solid Oxygen - Kamaruddin, KH; Abedin, AFZ; Zabidi, NA; Yahya, MZA; Taib, MFM; Rosli, AN (Polish Acad Sciences Inst Physics, 2024)
The electronic structures of 5-phase of solid oxygen (O-2)(4) are studied within the framework of density functional theory. The intriguing molecule has been known to have magnetic properties at room temperature by applying pressure. Nevertheless, until now there was no evidence of band structure studied in the anti-ferromagnetic behaviour of (O-2)(4). We report a comparison study for spin and non-spin polarization orbital which suggests that this ferromagnetic configuration of (O-2)(4) could not be seen experimentally, and antiferromagnetic configuration of (O-2)(4) was seen at higher pressure of about 10 GPa. The antiferromagnetic state transforms into the superconducting state as the sample temperature decreases. The results can serve as a useful approximation in studying general features of the electronic structure. The (O-2)(4) clusters are reported in the Raman study, having significant absorption at 1516 cm(-1) below infrared region.